PENGARUH IKLAN TERHADAP NIAT BELI KONSUMEN MELALUI CITRA MEREK DAN SIKAP PADA MINUMAN ISOTONIC MIZONE DI SURABAYA - Tanoni, Romy Victor (Kajian Ilmiah Mahasiswa Manajemen, 2012)
This study aims to determine the effect of Advertisement toward Purchase Intention through Brand Image and Attitude of Mizone Isotonic Drinks in Surabaya. The sampling technique used in this study was purposive sampling, where the sample was selected based on certain criteria that respondents residing in Surabaya, at least 17 years old, had saw the ad, bought and used a Mizone Isotonic drinks. The samples used in this study of 150 respondents. The data analysis techniques in this study used SEM (Structural Equation Modeling) and data processed using the program LISREL to analyze influence advertisement toward purchase intention through brand image and attitude. The results of this study indicate that there is a positive influence of advertisement to brand image, there is the influence advertisement to attitude, there is the influence brand image to attitude, there is the influence attitude to purchase intention, advertisement there is the influence to purchase intention through brand image and attitude